PWE-035 Can measurement of faecal haemoglobin assist in the assessment of iron deficient anaemia?. (17th June 2017) - Robinson, E; Digby, J; Strachan, J; Steele, B; Mowat, C
Abstract : Introduction: Post-menopausal women and men with iron deficient anaemia (IDA) require investigation because they harbour a risk of underlying pathology such as cancer (1). We have demonstrated that in patients with colorectal symptoms referred from primary care an undetectable Faecal Haemoglobin (FHb), measured by a Faecal Immunochemical Test (FIT), can be a 'rule-out test' for underlying significant bowel disease (2). We wished to examine whether measurement of FHb could assist in the assessment of patients referred from primary care with IDA. Method: We prospectively recorded all referrals to the NHS Tayside Colorectal Service from December 2015 – September 2016. GPs were encouraged to request FIT at point of referral in all patients. We used each patients unique Community Health Index number (CHI) to link GP referrals to laboratory results, OGD and colonoscopy findings. The WHO definition of IDA was used (3). FHb concentrations were grouped into undetectable (<10 µg/g), detectable and >400 µg/g for purposes of analysis. Results: 3272 patients were referred. 416 were referred as IDA of which 397 were verified; of these, 214 submitted a FIT test. To date 191 patients have undergone endoscopic procedures. 161 have had both an OGD and colonoscopy. An additional 26 have had OGD only and 3 have had colonoscopy only. At colonoscopy, 26 (15%) had significant bowel disease; 15 had CRC, 9 High-risk adenoma (HRA) and 2 Inflammatory Bowel Disease ( IBD). At OGD, 2 had Upper Gastrointestinal Cancer (UGIC). 116/191 (60%) had undetectable FHb; of these, 5% had significant GI disease (2 had CRC and 4 had HRA). Using a cut-off of 'undetectable' FHb (<10 µg/g), gave Negative Predictive Values of 98%, 96%, 100%, 100% for CRC, HRA, IBD, UGIC. respectively. 75/191 (39%) had detectable FHb; of these 13 (17%) had significant disease; 4 CRC, 5 HRA, 2 IBD, 2 UGIC. 15/164 (7%) had FHb >400; of these 9 (60%) had significant bowel disease (9 CRC). A detectable FHb gave a Positive Predictive Value of 37.1% for CRC rising to 50% for any significant bowel disease. Conclusion: Measurement of FHb is of benefit in the assessment of IDA. As concentrations rise, the likelihood of significant underlying GI disease increases from 5% (undetectable) to 39% (detectable) to 60% (very high). Those with high concentrations of FHb should be prioritised for urgent investigations as the likelihood of significant pathology is high. Disclosure of Interest: None Declared